User Satisfaction Mediates Ease of Use and Loyalty in Hulu Migas E-Procurement - Parlindungan, Purbanuara; Sanny, Lim; Zaroni , Zaroni; Sholiha, Sita Anisah (Studi Akuntansi, Keuangan, dan Manajemen, 2025)
Purpose: This study investigates how Ease of Use in an e?procurement system impacts User Loyalty within a national upstream oil and gas company, with User Satisfaction serving as a mediating factor. The aim is to clarify the indirect effect of system usability on loyalty by evaluating the mediation pathway through satisfaction Methodology: Employing a quantitative approach, data were collected from 296 e?procurement users across 15 national hulu migas companies using structured surveys. Responses were analyzed using Structural Equation Modeling (SEM) via SmartPLS 4 Results: The study found that ease of use significantly impacts user satisfaction (? = 0.779, p < .000) and user loyalty (? = 0.293, p < .000), with user satisfaction mediating the relationship between ease of use and loyalty (indirect effect = 0.537, p = .000). These results align with recent research indicating that ease of use enhances user satisfaction and loyalty, with satisfaction serving as a mediator in this relationship. Conclusions: Ease of use significantly effect on user satisfaction and loyalty. User satisfaction has positive and significant mediating ease of use and loyalty. Limitations: The study does not account for variations across different platforms or consider deeper system factors such as security, technical complexity, and usability challenges—issues highlighted in the literature as significant barriers to e-procurement adoption Contribution: This Research contributes to both management practice and academic understanding by showing that improving system usability can enhance loyalty through user satisfaction—offering a clear direction for strategic enhancements in e?procurement platforms.